Land resources usage and agricultural production organization for resettled people in Son La hydro-electric power station project - Tran, Van Tuan (VNU, 2014)
Recently, the resettlement activities of Son La hydroelectric power station (SHPS) have been carrying out within three provinces; Son La, Lai Chau, and Dien Bien......